2015
DOI: 10.1177/1468794115619002
|View full text |Cite
|
Sign up to set email alerts
|

Queer de-participation: reframing the co-production of scholarly knowledge

Abstract: This article critically examines the play of power in the co-production of scholarly knowledge in the context of a queer, feminist Participatory Action Research (PAR) project. By unpacking the power relations inherent in crafting a narrative of a collective project for a broader audience, we consider the conflicts, silences, and erasures that we experienced as participants, gatekeepers, and co-authors. We analyze iterations of a co-produced conference and journal article papers to recall the power dynamics tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…Like the journeys, workshops were accessible and both a “live” and “inventive” method of co‐production (Tarr et al., , p. 37) that actively engages academic collaborators and collaborators labelled/with disabilities. Working together, research is in‐process, dialogic, but also embodied and enacted (Bain & Payne, ). Exercises such as “I love, I hate, I dream” are a means by which to share pleasurable and painful experiences of life in the city, and make space for new forms of communication among all collaborators and the expression of feelings.…”
Section: The My Life In the City Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the journeys, workshops were accessible and both a “live” and “inventive” method of co‐production (Tarr et al., , p. 37) that actively engages academic collaborators and collaborators labelled/with disabilities. Working together, research is in‐process, dialogic, but also embodied and enacted (Bain & Payne, ). Exercises such as “I love, I hate, I dream” are a means by which to share pleasurable and painful experiences of life in the city, and make space for new forms of communication among all collaborators and the expression of feelings.…”
Section: The My Life In the City Projectmentioning
confidence: 99%
“…Attending to issues of power and space (mrs kinpaisby, ) and the politics of co‐production, we were concerned not to reproduce in the project the lack of control collaborators labelled/with intellectual disabilities reported experiencing in their own lives. What matters here is the shifting positioning of collaborators labelled/with disabilities over the course of the project, “how participation and collaboration are enacted and how power is embodied” (Bain & Payne, , p. 332). The mix of methods and activities produced a fluid positioning of all collaborators (Bigby et al., ), responsive to the evolving nature of the project, that disrupts to varying degrees typical power imbalances in qualitative research.…”
Section: Negotiating Tensions In Participatory Workmentioning
confidence: 99%
“…Approaches to coproduction have recognised that citizen and stakeholder perspectives can provide a valuable contribution to the generation of knowledge, particularly in areas of complexity (Defila and Di Giulio 2015;Polk 2015;Reyers et al 2015;Yeh 2016). Co-production in research that seeks to drive changes in the way knowledge is produced and applied has been developed through feminist and activist scholarship (Bain and Payne 2016;Jones et al 2017). Our understanding of migrant and minority disadvantage in housing has benefitted from the collaborative approach between practitioners and academics.…”
Section: Methodsmentioning
confidence: 99%
“…Hence if a project is community development rather than research, notions of 'research quality criteria' are likely to be absent. Some ECRs felt that while there were overlaps between community development and research, each could be relevant at distinct stages of a project: Other co-produced research has found that different phases of a project may have more or less coproduction; for instance 'analytic' stages (such as data analysis and writing-up) remain the remit of the academics (Bain and Payne, 2016), despite being central to knowledge construction (Nind, 2011;354).…”
Section: Overlapping Quality Debates In Research Co-production and Comentioning
confidence: 99%